Leading for Resilience and Equity: The Role of Innovative School Leadership in Mitigating Crisis and Fostering Inclusive Learning Environments - Choiruddin Choiruddin; Bounmy Xaypanya; Sulistyorini Sulistyorini (International Journal of Educational Narratives, 2026)
Background: The COVID-19 pandemic and ongoing educational crises have exposed the inadequacy of traditional leadership models in maintaining continuity and inclusivity. Purpose: This study aims to explore how innovative school leadership strategies can promote resilience and equity while ensuring access for all students during disruptions. Method: A mixed-methods research design was implemented, integrating quantitative surveys with qualitative case studies of school leaders in crisis-prone regions. Results: The findings identified that leadership strategies focusing on flexibility, staff training, and community engagement significantly improved school resilience and marginalized student participation. Conclusion: The study concludes that a holistic and adaptive leadership approach is essential for maintaining equitable educational opportunities and building crisis-resilient school systems.